Patterns of treatment and outcome with 500-mg fulvestrant in postmenopausal women with hormone receptor-positive/HER2-negative metastatic breast cancer: a real-life multicenter Italian experience - Raffaella Palumbo; Federico Sottotetti; Erica Quaquarini; Anna Gambaro; Antonella Ferzi; Barbara Tagliaferri; Cristina Teragni; Luca Licata; Francesco Serra; Pietro Lapidari; Antonio Bernardo (Therapeutic Advances in Medical Oncology, 2019)
Background: Fulvestrant 500 mg (F500) is the most active endocrine single agent in hormone receptor-positive (HR+)/HER2-negative metastatic breast cancer (MBC). Few data are available regarding the effectiveness of the drug in a real-world setting. Patients and methods: This prospective, multicenter cohort study aimed to describe the patterns of treatment and performance of F500 in a large population of unselected women with MBC, focusing on potential prognostic or predictive factors for disease outcome and response. The primary endpoints were progression-free survival (PFS) and clinical benefit rate. Results: From January 2011 to December 2015, 490 consecutive patients treated with F500 were enrolled. Overall, three different cohorts were identified and analyzed: the first received F500 after progression from previous chemotherapy (CT) or endocrine therapy; the second received the drug for de novo metastatic disease; and the third was treated as maintenance following disease stabilization or a response from a previous CT line. Median overall survival (OS) in the whole population was 26.8 months, ranging from 32.4 in first line to 22.0 and 13.7 months in second line and subsequent lines, respectively. Both the presence of liver metastasis and the treatment line were significantly associated with a worse PFS, while only the presence of liver metastasis maintained its predictive role for OS in multivariate analysis. Conclusions: The effectiveness of F500 was detected in patients treated both upon disease progression and as maintenance. The relevant endocrine sensitivity of 80% of patients included in the study could probably explain the good results observed in terms of outcome.